The Influence of Short-Distance Sprint Training on Physical Condition and Speed Performance in Youth Volleyball Players - Evi Saputri Romandoni; Agung Wahyudi; Yovhandra Ockta (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Volleyball is a sport that requires high levels of speed and endurance, making targeted physical training essential for optimal performance. Sprint training over distances of 50 and 80 meters is one approach that can enhance both attributes. This study investigates the effects of 50-meter and 80-meter sprint training on the speed performance of volleyball players involved in extracurricular activities at MAN 2 Banjarnegara. A quantitative experimental design was employed, utilizing a Two-Group Pretest-Posttest framework. Participants were randomly assigned to two experimental groups: Group A (50-meter sprint training) and Group B (80-meter sprint training). Across 14 training sessions, including pretest and posttest assessments, data were collected using a 60-meter sprint test. Statistical analyses included normality tests (Kolmogorov-Smirnov and Shapiro-Wilk), homogeneity tests, and paired t-tests. Results demonstrated that both sprint training protocols significantly improved sprint performance. Group A exhibited a mean improvement of 0.35 seconds, while Group B showed a greater improvement of 0.77 seconds, with both outcomes achieving statistical significance (p < 0.05). These findings indicate that sprint training over both distances effectively enhances speed performance in volleyball playersThe study concludes that incorporating 50-meter and 80-meter sprint training into volleyball conditioning programs can positively impact players' physical speed. Coaches and trainers are encouraged to integrate these sprint protocols to improve essential skills such as spiking, passing, and blocking. For comprehensive development, sprint training should be complemented with agility drills and aerobic endurance exercises to meet the multifaceted physical demands of the sport. Keywords: Volleyball, Physical Fitness, Extracurricular, Sports Student, Athletes.